(untitled) (Scientific journal of the Fergana State University, 2023)
In the interpretation of the image of Mashrab in the story “Singan setor” by Mirkarim Osim the matters on the historical truth and fictional composition have been considered, thus, revealing the skills of illustrating a historical image.